Dose‑dependent effects of cobalt chloride supplementation in a rat model of acetic acid‑induced ulcerative colitis (2024)
Several recent studies have shown that hypoxia preconditioning, often mimicked by sub-toxic levels of cobalt, can protect body tissues against various types of inflammatory and oxidative injuries. The present study was designed to understand the effects of low-to-moderate doses of cobalt chloride (CoCl2) on ulcerative colitis induced by acetic acid in male Wistar rats. Rats were pre-treated with CoCl2 at 10, 30 and 60 mg/kg BW for 7 days prior to, and later along with intra-rectal administration of 4% acetic acid for another 3 days. Rats were euthanized and the colons were examined macroscopically, and histologically, haematological parameters were evaluated in the blood and various oxidative stress parameters and inflammatory cytokines were studied in the colon and blood. Pre-treatment with CoCl2 at 10 mg/kg caused reduction in colonic levels of hydrogen peroxide (H2O2), nitric oxide (NO), advanced oxidation protein products (AOPP) and reduced serum TNF-α, but increased serum IL-10 levels. Conversely, rats treated with higher doses of CoCl2 showed exacerbation of macroscopic scores and histologic damage in the colon, with significantly elevated levels of oxidants and serum TNF-α along with reduced serum IL-10 levels. Values of all the measured haematological parameters (PCV, Hb, RBC, WBC and platelet count) were dose-dependently increased with increasing doses of CoCl2. The results of this study showed that consumption of cobalt at low doses could play a vital role in the control of ulcerative colitis, while higher doses can contribute to exacerbation of intestinal inflammation. Monitoring of cobalt concentrations in food and water consumed by ulcerative colitis patients is imperative to prevent exacerbation of colonic inflammation by cobalt.